Clinical Improvement in Knee Osteoarthritis Patients Supplemented with Nutritional Formula with Botanic Actives & Micronutrients; Supporting Joint Health: A Randomized, Double-Blind, Placebo-Controlled Clinical Study - Suryawanshi, Ashish; Kumar, Shashi; Ganu, Gayatri; Nagore, Dheeraj; Joshi, Susheel (International Journal of Innovative Research in Medical Science, 2024)
Background and objective: Osteoarthritis (OA) is characterized by the progressive degradation of articular cartilage, bone hypertrophy, subchondral sclerosis, and synovial changes. This study evaluates the efficacy of nutritional formula in repairing damaged cartilage and alleviating knee OA symptoms. Methods: The clinical trial enrolled 54 participants in a randomized, double-blind, placebo-controlled design, assigning them to a nutritional formula (Test) or Placebo in a 1:1 ratio for 90 days. Results: The study results showed the efficacy of nutritional formula treatment in alleviating symptoms of knee osteoarthritis. By day 90, significant reductions in pain (66.87%), stiffness (65.22%), and physical function impairment (67.19%) were observed. Notably, the substantial improvements in range of motion (8.85%) were observed, indicating enhanced joint mobility. Moreover, the nutritional formula led to reductions in joint swelling, tenderness, and warmth, along with decreased levels of inflammatory markers such as CRP, IL6, and ESR. Improved quality of life and exhibited excellent tolerability, with relief of more gastrointestinal symptoms reported compared to placebo. Furthermore, a reduction (32.84%) in fatigue levels was observed in the test group. Importantly, experienced adverse events were unrelated to the investigational products, affirming the safety profile of the nutritional formula. Conclusion: Nutritional formula presents promising analgesic, anti-inflammatory effects and shows potential for cartilage regeneration, offering a viable therapeutic option for managing knee OA. Further investigation is warranted to fully elucidate its mechanisms and optimize its clinical application.